2003
DOI: 10.1107/s1600536803001922
|View full text |Cite
|
Sign up to set email alerts
|

Bis(μ-8-hydroxy-7-iodoquinoline-5-sulfonato-κ3N,O:O′)bis[triaquazinc(II)] tetrahydrate

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean '(C±C) = 0.004 A Ê R factor = 0.028 wR factor = 0.061 Data-to-parameter ratio = 17.0For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
4
7
0
Order By: Relevance
“…The coordination of the Mg 2+ ion is distorted octahedral, consisting of N (N1) and O (O4) atoms of the oxine ring, one of the O (O3 i ) (symmetry code as in Table 1) atoms of a sulfonate group and three water molecules ( Fig. The bond distances and angles (Table 1) in this complex agree with those in related sulfonate complexes (Cai et al, 2001;Cameron et al, 1990;Francis et al, 2003b). The bond distances and angles (Table 1) in this complex agree with those in related sulfonate complexes (Cai et al, 2001;Cameron et al, 1990;Francis et al, 2003b).…”
Section: Commentsupporting
confidence: 75%
See 1 more Smart Citation
“…The coordination of the Mg 2+ ion is distorted octahedral, consisting of N (N1) and O (O4) atoms of the oxine ring, one of the O (O3 i ) (symmetry code as in Table 1) atoms of a sulfonate group and three water molecules ( Fig. The bond distances and angles (Table 1) in this complex agree with those in related sulfonate complexes (Cai et al, 2001;Cameron et al, 1990;Francis et al, 2003b). The bond distances and angles (Table 1) in this complex agree with those in related sulfonate complexes (Cai et al, 2001;Cameron et al, 1990;Francis et al, 2003b).…”
Section: Commentsupporting
confidence: 75%
“…In the crystal structure of tetraaquabis(hydroxymethanesulfonato)magnesium(II), the sulfonate group and water molecules are involved in coordination (Cameron et al, 1990), whereas in the three other crystal structures, namely hexaaquamagnesiumbis(8-anilino-1-naphthalenesulfonate) hexahydrate (Cody & Hazel, 1977), hexaaqua(1,5-napthalenedisulfonato)magnesium (Cai et al, 2001) and the magnesium salt of 7-hydroxy-8-(phenylazo)-1,3-naphthalenedisulfonic acid (Ojala et al, 1994), the sulfonate groups are not involved in coordination and the metal atoms are surrounded only by water molecules. This has been observed in the ferron complexes of nickel (Raj et al, 2003), cobalt (Balasubramanian, 1995) and zinc (Francis et al, 2003b), and in the title compound, (I). In one type, the organic ligands are stacked over one another, each pair of adjacent members of the stack being inversion related.…”
Section: Commentmentioning
confidence: 71%
“…Hydrogen-bonding patterns involving aryl sulfonates and their metal complexes are of contemporary interest Cai, Chen, Liao, Yao et al, 2001;Onoda et al, 2001). Hydrogen-bonding patterns of sulfoxines (Balasubramanian & Muthiah, 1996a,b) and metal sulfoxinates (Baskar Raj et al, 2001, 2003Francis et al, 2003;Murugesan & Muthiah, 1997) have also been reported from our laboratory. In the course of our efforts to prepare a mixed-ligand complex of sodium involving 8-hydroxyquinoline-5-sulfonic acid and 4,4 Hbipyridine, which have been extensively used as building units in the crystal engineering of many supramolecular structures (Dong et al, 2002;Fu et al, 2000), we obtained the title complex, (I).…”
Section: Commentsupporting
confidence: 70%
“…In the Na complex of HQS, all the O atoms of the sulfonate group are involved in coordination, along with bidentate chelation of the oxine ring (Raj et al, 2002). The crystal structures of Ni (Raj et al, 2003), Zn (Francis et al, 2003) and Co (Balasubramanian, 1995) complexes of 8-hydroxy-7-iodoquinoline-5-sulfonate (ferron) have also been reported from our laboratory. They are isomorphous and have cage-like dimeric motifs.…”
Section: Commentmentioning
confidence: 89%